2015
DOI: 10.2174/1570159x13666150825220524
|View full text |Cite
|
Sign up to set email alerts
|

An Endogenous Tachykinergic NK2/NK3 Receptor Cascade System Controlling the Release of Serotonin from Colonic Mucosa

Abstract: 5-Hydroxytryptamine (5-HT) released from colonic mucosal enterochromaffin (EC) cells is a major signaling molecule, which participates in the pathophysiological regulation of colonic functions in gut disorder including irritable bowel syndrome (IBS), but the endogenous modulator system for the 5-HT release is not yet well elucidated. Our in vitro studies in guinea-pig colon have indicated that the cascade pathway of neuronal tachykinergic NK3 receptors and NK2 receptors on peptide YY (PYY)-containing endocrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In this way, the presence of low amounts of PYY and low densities of PYY cells in the large intestine will impair the release of PYY, contributing to the dysmotility that is associated with IBS in that this hormone inhibits gastric and pancreatic secretion, delays the emptying of the stomach, and increases water and electrolyte absorption ( 88 ). Moreover, inferred from the fact that PYY modulates 5-HT release, which regulates visceral sensitivity, the low PYY concentration could indirectly contribute to IBS symptoms of visceral hypersensitivity ( 89 ). It has been reported that the consumption of LFD increases the PYY cell density to the normal level in IBS patients and improves the symptoms of IBS as well ( 82 ); in a similar manner, SCFAs, one of the fermentation products of intestinal microbes, have been reported to promote gene expression and stimulate the production of PYY ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the presence of low amounts of PYY and low densities of PYY cells in the large intestine will impair the release of PYY, contributing to the dysmotility that is associated with IBS in that this hormone inhibits gastric and pancreatic secretion, delays the emptying of the stomach, and increases water and electrolyte absorption ( 88 ). Moreover, inferred from the fact that PYY modulates 5-HT release, which regulates visceral sensitivity, the low PYY concentration could indirectly contribute to IBS symptoms of visceral hypersensitivity ( 89 ). It has been reported that the consumption of LFD increases the PYY cell density to the normal level in IBS patients and improves the symptoms of IBS as well ( 82 ); in a similar manner, SCFAs, one of the fermentation products of intestinal microbes, have been reported to promote gene expression and stimulate the production of PYY ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the hypothalamus, the neurokinin B is co-expressed with kisspeptin [52], a neuropeptide involved in 5-HT turnover stimulation [53]. Neurokinin B and kisspeptin showed also a cooperative mechanism at the neuroendocrine level [54], whereas the activation of NK3R triggered colon 5-HT release, especially in pro-inflammatory conditions [55]. Interestingly, in our ex vivo model, the cortexes exposed to the neurotoxic stimulus showed a supra-physiological 5-HT overflow and subsequent increase in 5-HT turnover.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining two RCTs showed the effect of ramosetron and antidepressants for symptoms of IBS [ 28 , 37 ]. There were four in vitro trials included in the review [ 15 , 18 , 23 , 24 ]. One of those in vitro trials showed how NK2/NK3 receptors control serotonin release [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
“…There were four in vitro trials included in the review [ 15 , 18 , 23 , 24 ]. One of those in vitro trials showed how NK2/NK3 receptors control serotonin release [ 15 ]. One of the in vitro trials discussed the serotonin reuptake transporter (SERT) and IBS relationship [ 18 ], and the remaining two in vitro trials displayed how tumor growth factor-beta one and glucagon-like peptide-1 modulate SERT transcription, respectively [ 23 , 24 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation